1976
DOI: 10.1111/j.1469-8137.1976.tb01475.x
|View full text |Cite
|
Sign up to set email alerts
|

SEQUESTRATION OF CYTOPLASMIC ORTHOPHOSPHATE BY MANNOSE AND ITS DIFFERENTIAL EFFECT ON PHOTOSYNTHETIC STARCH SYNTHESIS IN C3 AND C4 SPECIES

Abstract: SUMMARYLeaf tissues from many C3 species respond to exogenous mannose in the light by a marked stimulation of starch synthesis. This is attributed to a decreased movement of triose phosphate from the chloroplast following sequestration of cytoplasmic orthophosphate as mannose phosphate and interference with the phosphate translocator. By contrast, in most C4 species, feeding of mannose inhibits starch synthesis. It is concluded that, in these plants, the principal effect of sequestration of orthophosphate is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 41 publications
5
40
0
Order By: Relevance
“…A similar effect, the increase of mannose-6-phosphate with a concomitant decrease in inorganic phosphate, was observed for plants incubated on mannose (Loughman et al, 1989). Sheu-Hwa et al (1975) and Herold et al (1976) found an accumulation of starch in some plant species incubated on mannose. These authors speculated that the sequestration of inorganic phosphate by mannose-6-phosphate accumulation caused a reduction in the activity of the triose-phosphate translocator, thereby reducing the export of carbon from the chloroplast and inhibiting starch degradation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A similar effect, the increase of mannose-6-phosphate with a concomitant decrease in inorganic phosphate, was observed for plants incubated on mannose (Loughman et al, 1989). Sheu-Hwa et al (1975) and Herold et al (1976) found an accumulation of starch in some plant species incubated on mannose. These authors speculated that the sequestration of inorganic phosphate by mannose-6-phosphate accumulation caused a reduction in the activity of the triose-phosphate translocator, thereby reducing the export of carbon from the chloroplast and inhibiting starch degradation.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast to glucose, mannose is known to be toxic for plant growth, supposedly due to a sequestration of inorganic phosphate as mannose-6-phosphate (Herold et al, 1976;Sheu-Hwa et al, 1975). Similarly, galactose is highly toxic when supplied exogenously to plants in concentrations of 1-10 mM (Loughman et al, 1989;Maretzki and Thom, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In sugar beet, mannose did not reduce the sucrose level in the manner expected from reports in the literature (5,10,13,14); however, it did cause a reduction in exogenous ['4C]sucrose influx. In addition, mannose pretreatment prevented, in some way, the change in partitioning of exogenously supplied ['4C]sucrose, which was found to occur following the removal of sink activity (31).…”
supporting
confidence: 55%
“…Since the transport of Pi between the vacuole and cytosol is thought to be slow (23, 27; but see Ref. 16), the addition of mannose effects a sequestration ofcytosolic Pi (5,13; but cf Ref. 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation